2005
DOI: 10.1073/pnas.0502257102
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 regulates the zinc transporter Zip14 in liver and contributes to the hypozincemia of the acute-phase response

Abstract: Infection and inflammation produce systemic responses that include hypozincemia and hypoferremia. The latter involves regulation of the iron transporter ferroportin 1 by hepcidin. The mechanism of reduced plasma zinc is not known. Transcripts of the two zinc transporter gene families (ZnT and Zip) were screened for regulation in mouse liver after turpentine-induced inflammation and LPS administration. Zip14 mRNA was the transporter transcript most up-regulated by inflammation and LPS. IL-6 knockout (IL-6 ؊/؊ )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
395
1
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(441 citation statements)
references
References 40 publications
21
395
1
14
Order By: Relevance
“…Bacteria are thought to contain high-affinity zinc transporters as a strategy to overcome zinc limitation during infection in which the acute phase response has been shown to result in reduced plasma zinc concentrations (20,38) with upregulation and release of the zinc binding complex calprotectin in the blood and lungs (29,31,55). In accord with this hypothesis, we demonstrated here that H. influenzae requires a specialized high-affinity zinc utilization pathway for virulence.…”
Section: Discussionsupporting
confidence: 76%
“…Bacteria are thought to contain high-affinity zinc transporters as a strategy to overcome zinc limitation during infection in which the acute phase response has been shown to result in reduced plasma zinc concentrations (20,38) with upregulation and release of the zinc binding complex calprotectin in the blood and lungs (29,31,55). In accord with this hypothesis, we demonstrated here that H. influenzae requires a specialized high-affinity zinc utilization pathway for virulence.…”
Section: Discussionsupporting
confidence: 76%
“…Nukina et al showed that the plasma IL-6 level peaked at 1 h after the onset of restraint stress in the mouse but they did not measure the value at 3 h (Nukina et al 2001). After this serum IL-6 elevation, mRNA of Zip14, an IL-6 responsive zinc transporter which facilitates extracellular zinc into cytosol (Liuzzi et al 2005), was induced about 12-fold at 6 h after the onset of restraint stress (Fig. 2a), followed by the increase in the zinc concentration in the liver (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ZIP members facilitate zinc influx into the cytosol, while CDF members facilitate its efflux from the cytosol. Abundance of Zip14, one of the ZIP family transporters, in the plasma membrane of hepatocytes is induced after turpentine-induced inflammation and lipopolysaccharide administration (Liuzzi et al 2005). IL-6 is considered to be the main proinflammatory cytokine regulating acute-phase genes and Zip14 expression is up-regulated through IL-6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Zinc status in patient with suspected zinc deficiency can be assessed from several biological materials with the most common being plasma/serum blood samples or urine samples. 9 However, plasma/serum zinc status is not only influenced by zinc deficiency, also inflammation can lower plasma zinc levels 10 and as such interpretation of plasma zinc levels is not always straightforward. 11,12 Methods for the analysis of plasma or serum zinc concentrations range from atomic absorption spectrophotometry over mass spectrometry to the more commonly used photometry.…”
Section: Introductionmentioning
confidence: 99%